Applications of the Kharkov potential in the theory of nuclear forces and nuclear reactions - Arslanaliev, A.; Kamada, H.; Shebeko, A.; Stepanova, M.; Witala, H.; Yakovlev, S. (Вопросы атомной науки и техники, 2018)
The Kharkov potential is a recent field theoretical model of nucleon-nucleon (NN) interaction that has been built
up in the framework of the instant form of relativistic dynamics starting with the total Hamiltonian of interacting
meson and nucleon fields and using the method of unitary clothing transformations (UCTs). The latter connect the
representation of “bare” particles (BPR) and the representation of “clothed” particles (CPR), i.e., the particles with
physical properties. Unlike many available NN potentials each of which is the kernel of the corresponding nonrelativistic Lippmann-Schwinger (LS) equation this potential being dependent in momentum space on the Feynman-like
propagators and covariant cutoff factors at the meson-nucleon vertices is the kernel of relativistic integral equations
for the NN bound and scattering states. We show our calculations with the Bonn and Kharkov potentials for such
quantities as the phase shifts in the neutron-proton scattering up to the pion production threshold, the binding energies of deuteron and triton, the nucleon momentum distributions in these nuclei and some Nd elastic scattering observables. Special attention is paid to finding from the contemporary n-p phase shift analysis some optimum values
of the adjustable parameters included. Харківський потенціал, у недавній час запропонована теоретико-польова модель нуклон-нуклонної (NN)
взаємодії, був побудований в рамках так званої миттєвої форми релятивістської динаміки, маючи гамільтоніан взаємодіючих мезонних і нуклонного полів і використовуючи метод унітарних одягаючих перетворень.
Ці перетворення пов'язують зображення “голих” частинок з зображенням “одягнених” частинок, тобто частинок з спостережуваними (фізичними) властивостями. На відміну від багатьох NN-потенціалів, кожен з
яких є ядром відповідного нерелятивістського рівняння Ліпмана-Швінгера, цей потенціал, що залежить у
імпульсному просторі від фейнман-подібних пропагаторів і коваріантних обрізуючих факторів у мезоннуклонних вершинах, є ядром релятивістських інтегральних рівнянь для NN-пов'язаних станів і станів розсіювання. Ми покажемо наші обчислення з Боннським та Харківським потенціалами для таких величин, як
фазові зрушення в нейтрон-протонному розсіюванні до порога народження піонів, енергій зв'язку дейтрона і
тритона, імпульсних розподілів нуклонів у цих ядрах і деяких спостережуваних у пружному Ndрозсіюванні. Особлива увага приділяється визначенню з сучасного n-p-фазового аналізу оптимальних значень для підгоночних параметрів. Харьковский потенциал, недавно предложенная теоретико-полевая модель нуклон-нуклонного (NN) взаимодействия, был построен в рамках так называемой мгновенной формы релятивистской динамики, имея
гамильтониан взаимодействующих мезонных и нуклонного полей и используя метод унитарных одевающих
преобразований. Эти преобразования связывают представление “голых” частиц с представлением “одетых”
частиц, т.е. частиц с наблюдаемыми (физическими) свойствами. В отличие от многих NN-потенциалов, каждый из которых является ядром соответствующего нерелятивистского уравнения Липманна-Швингера, этот
потенциал, зависящий в импульсном пространстве от фейнман-подобных пропагаторов и ковариантных обрезающих факторов в мезон-нуклонных вершинах, является ядром релятивистских интегральных уравнений
для NN-связанных состояний и состояний рассеяния. Мы покажем наши вычисления с Боннским и Харьковским потенциалами для таких величин, как фазовые сдвиги в нейтрон-протонном рассеянии до порога рождения пионов, энергий связи дейтрона и тритона, импульсных распределений нуклонов в этих ядрах и некоторых наблюдаемых в упругом Nd-рассеянии. Особое внимание уделяется определению из современного np-фазового анализа оптимальных значений для подгоночных параметров.